Development of Radar and Navigation Radar Modules As A Learning Media Radar Course And Navigation In The Department Of Electrical Engineering, UNESA - Baskoro, Farid . (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2018)
AbstractRADAR (Radio Detection And Ranging) is a tool used to detect and know the distance of an object.Radar is one of the important tools in the world of telecommunications, shipping and in the militaryworld. So that the State University of Surabaya, especially the Department of Electrical Engineeringeducation set Radar and Navigation as One of the compulsory lecture that must be taken in the field ofcommunication electronics studies. In this study the author tries to develop teaching module to facilitatestudents in studying radar and navigation subjects. Where in the module consists of 7 chapters namelyRadar History, Radar Type, In Flight Radar, Navigation System, Infrastructure Radar, Hadware radar, andRadar Calibration and Radar Technique. The results of this module are then validated by expert lecturersand giving a student response questionnaire. Results for module validation by expert media obtained anaverage score of 84.06% for student responses in an average score of 83.21%. Based on the above datacan be stated that the module is suitable to be used as one of the reference and can be accepted by thestudents.Keywords: Radar. Radar Type, Teaching Module, Radar Infrastructure